Analysis of Political News in the Greek Stock Market - Takkides, Themistoklis (2013)
This research paper examined the relationship between political news and stock market returns and volatility in the Greek stock market using the EGARCH in mean framework. The APARCH model is also utilised in order to capture the persistence effect of news. In order to carry out this investigation daily data of the Athens Stock Exchange General Price Index (ASEGPI) were obtained using DataStream. Results indicate that returns are unaffected by the release of political news, whilst the conditional variance is affected only from the release of negative news. The EGARCH in mean also reveals the existence of leverage effect, which means that positive news generate higher volatility for ASEGPI rather than negative. The persistence effect, through the APARCH model, is also evidenced in ASEGPI that is the long memory of the stock market. Finally, risk–return trade-off is absent in this market therefore, investors are not rewarded for their exposure to risk.